The poet's butler: the process of invisibility of the visual artist Luiz Raphael Domingues Rosa, guardian of the memory of Augusto dos Anjos (Tempo e Argumento, 2024)
This article discusses the decisive role played by the artist Luiz Raphael Domingues Rosa (1945-2007) in the process of identifying the poet Augusto dos Anjos (1884-1914) as a heritage site of the city of Leopoldina, Minas Gerais. It analyzes his work as a collector of the poet and of the history of Leopoldina itself, as well as his appropriation of the house where Augusto dos Anjos lived in that city in 1914, by giving it the meaning of a memorial, inaugurating the “Espaço dos Anjos” there in 1983. The “Espaço dos Anjos” functioned as a combination of museum, studio and art school, closing its activities in 2007 with the death of Luiz Raphael. The house was reopened to the public in 2012, under the management of the municipal administration, as the “Espaço dos Anjos Museum”, exclusively exhibiting the collection of the poet from Paraíba. In this moment of transition, in which the institutionalization of the museum dedicated to Augusto dos Anjos is taking place, a process of erasure of the figure of the collector Luiz Raphael can be observed, a fact that is problematized considering the hypothesis that it is the result of prejudices in relation to the artist, whether due to his dissident persona or insurgent artistic-cultural activity.
Keywords: Luiz Raphael Domingues Rosa; Augusto dos Anjos; Espaço dos Anjos Museum; Leopoldina/MG